2016
DOI: 10.18502/kms.v1i1.584
|View full text |Cite
|
Sign up to set email alerts
|

Free Vibration Analysis Of The Moderately Thick Laminated Composite Rectangular Plate On Two-Parameter Elastic Foundation With Elastic Boundary Conditions

Abstract: An improved Fourier series method is presented for the free vibration analysis of the moderately thick laminated composite rectangular plate with general elastic supports and point supports resting on an elastic foundation. The approach is based on the first order shear deformation theory and foundation effect using two-parameter Pasternak foundation model. The displacement and rotation functions are generally sought, regardless of boundary conditions, as Fourier series and supplementary functions. All the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In addition, as results from other studies have shown [1,3,26,27,28,29,30,31,32,33,34], the main source of noise generated by the gear transmission is its housing and, in particular, its upper lid. Modification of the upper housing by introducing additional ribs significantly contributed to a reduction of its vibroactivity [1,29].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, as results from other studies have shown [1,3,26,27,28,29,30,31,32,33,34], the main source of noise generated by the gear transmission is its housing and, in particular, its upper lid. Modification of the upper housing by introducing additional ribs significantly contributed to a reduction of its vibroactivity [1,29].…”
Section: Introductionmentioning
confidence: 92%
“…Modification of the upper housing by introducing additional ribs significantly contributed to a reduction of its vibroactivity [1,29]. Another solution that is recommended to minimize the vibroactivity of the gear housing is to modify its wall thickness [28,32]. Increasing the wall thickness leads to a significant reduction in the vibroactivity of the gearbox; however, at the expense of increasing the weight of the housing.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers who have worked on the plate on elastic foundation problem are: Althobaiti and Prikazchikov [18]; Zhong, Zhao and Hu [19]; Li, Zhong and Li [20]; Li, Zhong and Tian [21]; Li et al [22]; Zhang, Shi and Wang [23]; Agarana, Gbadeyan and Ajayi [24]; Are, Idowu and Gbadeyin [25]; Agarana and Gbadeyin [26]; Tahuoneh and Yas [27]; and Ye et al [28].…”
Section: H B mentioning
confidence: 99%
“…In order to explain the innovation of this paper more intuitively, a brief illustration is given in Figure 3. Compared with [30,66], this paper has three main original ideas. Firstly, this paper focuses on the effect of elastic foundation on the plate.…”
Section: Displacement Expressionmentioning
confidence: 99%